Transformation of Magnaporthe grisea to phosphinothricin resistance using the bar gene from Streptomyces hygroscopicus - Hei Leung; Pat Loomis; Martin L. Pall (Fungal Genetics Reports, 1995)
Three transformation systems have been reported for the rice blast fungus Magnaporthe grisea (Parsons et al. 1987 Proc. Natl. Acad. Sci. USA 84:4161-4165; Daboussi et al. 1989 Curr. Genet. 15:453-456; Leung et al. 1990 Curr. Genet. 17:409-411). Among these three selection systems, only hygromycin B resistance provides a dominant selection that can be used for any wild type strain. A second dominant selection marker is needed to transform strains that are already hygromycin B resistant.